Factors influencing accountability practices in managing fund : the case of local NGOs in Yemen - Ahmed, Abdul Wahed Hamoud Abdullah (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2020)
Accountability has been one of the most problematic and prevalent issues for businesses across the globe for a long time. However, more attention and researches have been dedicated to the issue after the corporate accounting scandals of Enron, WorldCom and others. The increase in financial misappropriation and corporate scandals have had a significant influence on financial reporting interpretation and analysis as well as auditing and regulations. Poor economic management and governance by the Yemeni Government have resulted in donors shifting their attention and increasing funding to non-governmental organisations (NGOs) from the early 1990s. However, the NGOs are also facing with streams of frauds and corruptions, for example, individuals abusing disaster reliefs and donations. This raises a question on the accountability of these organisations. This study, therefore, seeks to investigate factors influencing the level of accountability practices of NGOs in Yemen. This study adopted a quantitative design. The population of the study consisted of local NGOs operating in Yemen. Data was obtained using a structured questionnaire. This study found that accountability was not widely practised among NGOs in Yemen. However, the level of accountability practices of these organisations was significantly influenced by the use of information and communication technology and the perceived motive that have a positive impact on practising accountability in Yemeni NGOs. Meanwhile, factors like size and human resources capabilities have a negative impact on accountability practices. The study also found that the level of practising accountability in Yemeni NGOs is moderate, which brings the study to recommend the formulation of policies by the relevant regulatory bodies to ensure that the NGOs enhance accountability for improved efficiency and transparency. It is also recommended to apply more social accountability by the community to make sure that the resources are well managed, and the services are delivered in an efficient and effective way.